Perancangan IT Blueprint Menggunakan TOGAF ADM untuk Mendukung Transformasi Digital pada UMKM - Berlian Maulidya Izzati; Asti Amalia Nur Fajrillah; Rahmania Arina Alkha Saputri; Ivana Tyora Oktavian; Lolly Asri Widyastri (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
MSMEs (Micro, Small and Medium Enterprises) have an essential role in helping the country in the economic sector. While there are several major problems faced by MSMEs, including manual financial records, no product standardization, and limited marketing scope. The solution to these problems is to align between MSME business goals and IT solutions that will be used. TOGAF (The Open Group Architecture Framework) is one of the best practices in making enterprise architecture that includes the design, planning, implementation and governance of IT-business that can be adjusted to the needs or problems in MSMEs. The case study of the application of TOGAF in this study used three food MSME objects, namely Kylafood, Maicih Chips and Bogares Beans with interview and observation methods. The enterprise architecture design for the MSME food category proposes that there are six main applications both utilizing existing applications and developing new applications, namely Microsoft Excel, e-marketplace, social media, the official MSME website, MSME operational management applications and accounting applications. The hardware that can support the application design are servers, routers, switches and PC / Mobile. With the support of IT systems and tools that are in line with business objectives, it is expected to be able to improve operational efficiency, reduce costs for marketing and increase profits for MSMEs